Faktor Pembentuk Intensi, Tujuan, dan Implementasi Kewirausahaan dalam Perspektif Theory of Planned Behavior - Agustian Zen; Silvy Sondari Gadzali; Kraugusteeliana Kraugusteeliana; Suherlan Suherlan (STKIP PGRI SITUBONDO, 2023)
Nowadays, entrepreneurship training is needed to foster students' entrepreneurial interest, such as from educational institutions. However, before someone is given training and instilled with an entrepreneurial mindset, it is first necessary to know the various factors that form entrepreneurial intentions. This research will provide empirical evidence that entrepreneurial intentions can be influenced through the Theory of Planned Behavior which boils down to goals and implementation. This study explains the constructs and propositions used as the basis for building a conceptual model using library research methods. This study arrives at a statement that the Theory of Planned Behavior is valid regarding context, flexibility, simplicity, and superior in its ability to predict a person's behavioral intention, goals, and implementation in entrepreneurship.